Economic perspectives on transport and equality - David Lewis (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2011)
Poverty, inequality and social exclusion are closely tied to personal mobility and the accessibility of goods and services. Evidence of the economic role of transport in promoting better living standards and greater wellbeing can be seen in the effects of both overall public investment in transport infrastructure, and in the impacts of specific transport policies, projects and multi-project plans.
Keywords: 330